2017
DOI: 10.3389/fpls.2017.00435
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Multivariable Agro-Physiological Parameters for Detecting Salt Tolerance of Wheat Cultivars under Simulated Saline Field Growing Conditions

Abstract: Field-based trials are crucial for successfully achieving the goals of plant breeding programs aiming to screen and improve the salt tolerance of crop genotypes. In this study, simulated saline field growing conditions were designed using the subsurface water retention technique (SWRT) and three saline irrigation levels (control, 60, and 120 mM NaCl) to accurately appraise the suitability of a set of agro-physiological parameters including shoot biomass, grain yield, leaf water relations, gas exchange, chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 47 publications
3
100
0
Order By: Relevance
“…The former stress diminishes the plants’ ability to benefit from water, similar to water-deficit-induced stress [ 10 , 11 ]. However, the latter stress leads to an energy problem in plants due to a significant reduction in photosynthetic capacity, different metabolic functions, and cell elongation [ 12 , 13 , 14 , 15 , 16 ]. Moreover, salinity stress leads to nutrient imbalance by reducing uptake of essential elements, particularly K + , Mg 2+ , and Ca 2+ , which causes ion imbalance at cellular and tissue levels [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The former stress diminishes the plants’ ability to benefit from water, similar to water-deficit-induced stress [ 10 , 11 ]. However, the latter stress leads to an energy problem in plants due to a significant reduction in photosynthetic capacity, different metabolic functions, and cell elongation [ 12 , 13 , 14 , 15 , 16 ]. Moreover, salinity stress leads to nutrient imbalance by reducing uptake of essential elements, particularly K + , Mg 2+ , and Ca 2+ , which causes ion imbalance at cellular and tissue levels [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the multiple physiological variables that result in a considerable decline in biomass production of plant under salt stress, gas exchange mechanisms and the photosynthetic capacity are the most important. Dramatic changes in leaf turgor pressure and a K + content deficit in leaf tissue under salt stress conditions lead to a significant decline in stomatal conductance (Gs), which then adversely affects photosynthesis (Pn) and transpiration (E) rates [1,2]. It is thus necessary to monitor the responses of these physiological variables to salt stress to enable improvements in the salt tolerance of wheat genotypes or apply appropriate agronomic management practices that alleviate the adverse impacts of salt stress, with the ultimate aim of providing sustainable crop production under salinity stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This is because this method can be applied on a large scale, can provide a long-term solution, and is inexpensive for poor farmers. However, success in improving salt tolerance of genotypes has been limited by a number of factors, such as limited sources of genetic diversity in breeding programs, low selection efficiency using simultaneous morpho-physiological and biochemical parameters as screening criteria, and the lack of effective evaluation methods to detect salt tolerance of genotypes using overall salinity levels and multivariable screening criteria [2][3][4][5][6].Many studies investigated the tolerance of wheat (Triticum aestivum L.) into the salinity and found that the tolerated genotypes can survive in the level of 150 mM NaCl [3,5]. High salinity lowers agricultural productivity.…”
mentioning
confidence: 99%
“…Multivariate analysis is a useful tool for identifying sources of genetic variation and discriminating their salt tolerance using accurate and multiple selection criteria. Therefore, a multivariate analysis combining morphological, physiological, and biochemical traits would be most appropriated [2,6,24,38].Therefore, the aims of our study were to characterize the genetic variance, heritability, and expected genetic advances of different traits as screening criteria for evaluating the salt tolerance of DHL genotypes under different salinity conditions. In addition, particular attention was paid to investigate the efficiency of using multivariable morpho-physiological and biochemical parameters as well as to identify traits that can be employed as credible screening criteria for the selection and improvement of salt tolerance in wheat.…”
mentioning
confidence: 99%
See 1 more Smart Citation